Online Exports and the Wage Gap - Cruz, Marcio; Milet, Emmanuel; Olarreaga, Marcelo (World Bank, Washington, DC, 2017)
The development of the Internet is often seen as a source of demand for skilled workers and therefore a potential driver of the wage gap between skilled and unskilled workers. This paper focuses on the impact that international trade in online platforms has on the wage gap. Because online trade allows smaller firms with relatively more unskilled workers to access world markets it can be expected a priori that an expansion of online exports reduces the wage gap. After correcting for potential endogeneity bias in a sample of 22 developing countries for which online trade and wage gap data can be matched, the study finds that a 1 percent increase in the share of online exports over GDP leads to a 0.01 percent decline in the wage gap.